Outcomes of Hospital at Home for Older Adults with and without High Levels of Social Support. (September 2021) - Augustine, Matthew R.; Siu, Albert L.; Boockvar, Kenneth S.; DeCherrie, Linda V.; Leff, Bruce A.; Federman, Alex D.
Abstract : The evaluation of social support within hospital at home (HaH) programs has been limited. We performed a secondary analysis of a prospective cohort evaluation of 295 participants receiving HaH care and 212 patients undergoing traditional hospitalization from November of 2014 to August of 2017. We examined the confounding and moderating effects of instrumental and informational social support upon length of stay and 30-day rehospitalization, emergency department (ED) visit, and skilled nursing facility admission. Instrumental social support attenuated the effects of HaH upon any ED visit (base model: OR 0.61, p = 0.037; controlling for social support: OR 0.71, p = 0.15). The association of HaH with other outcomes remained unchanged. Interactions between HaH and informational or instrumental social support for all outcomes were not significant. Lack of high levels of social support had little effect on the positive outcomes of HaH care, suggesting similar benefits of HaH services for patients with lower levels of social support.